2
$\begingroup$

What is the limit as $x$ approaches $0$ of: $$\frac{\sqrt{1+\tan x} - \sqrt{1+\sin x}}{1+x-\cos x}?$$

We cannot use L'Hôpital's rule or anything advanced like Taylor series. I reduced it to, by considering the numerator's conjugate:

$$\frac{1}{2}\lim_{x \to 0}\frac{\tan x - \sin x}{1+x-\cos x}$$

But I cannot go further. Please help.

EDIT: Thinking carefully, I think I can simplify further:

$$\frac{1}{2}\lim_{x \to 0}\frac{\frac{\tan x - \sin x}{x}}{\frac{1-\cos x}{x}+1}=\frac{1}{2}\lim_{x \to 0}\frac{\tan x - \sin x}{x}$$

And perhaps the solution:

$$\frac{1}{2}\lim_{x \to 0}\frac{\tan x - \sin x}{x}=\frac{1}{2}(\lim_{x \to 0}\frac{\tan x}{x} - 1)=\frac{1}{2}(\lim_{x \to 0}\frac{\sin x}{\cos x \cdot x}) - 1=\frac{1}{2}(1- 1)=0$$

Is this correct?

$\endgroup$
1
$\begingroup$

The title of the question is a bit intimidating as this limit involves very basic trigonometric manipulation and standard limits like $\lim\limits_{x \to 0}\dfrac{\sin x}{x} = 1$. Here goes the simple solution $$\begin{aligned}L &= \lim_{x \to 0}\frac{\sqrt{1 + \tan x} - \sqrt{1 + \sin x}}{1 + x - \cos x}\\ &= \lim_{x \to 0}\frac{\sqrt{1 + \tan x} - \sqrt{1 + \sin x}}{1 + x - \cos x}\cdot \frac{\sqrt{1 + \tan x} + \sqrt{1 + \sin x}}{\sqrt{1 + \tan x} + \sqrt{1 + \sin x}}\\ &= \lim_{x \to 0}\frac{\tan x - \sin x}{(1 + x - \cos x)(\sqrt{1 + \tan x} + \sqrt{1 + \sin x})}\\ &= \frac{1}{2}\lim_{x \to 0}\frac{\tan x - \sin x}{1 + x - \cos x}\\ &= \frac{1}{2}\lim_{x \to 0}\tan x\cdot \frac{1 - \cos x}{1 + x - \cos x}\\ &= \frac{1}{2}\lim_{x \to 0}\tan x\cdot \frac{2\sin^{2}(x/2)}{x + 2\sin^{2}(x/2)}\\ &= \lim_{x \to 0}\tan x\cdot \dfrac{\dfrac{\sin^{2}(x/2)}{(x/2)^{2}}\cdot(x/2)^{2}}{x + 2\dfrac{\sin^{2}(x/2)}{(x/2)^{2}}\cdot(x/2)^{2}}\\ &= \lim_{x \to 0}\tan x\cdot \frac{x}{4}\cdot\dfrac{\dfrac{\sin^{2}(x/2)}{(x/2)^{2}}}{1 + \dfrac{x}{2}\cdot\dfrac{\sin^{2}(x/2)}{(x/2)^{2}}}\\ &= 0\cdot 0\cdot\dfrac{1}{1 + 0\cdot 1} = 0\end{aligned}$$

$\endgroup$
2
$\begingroup$

$$\frac{\sqrt{1+\tan x} - \sqrt{1+\sin x}}{1+x-\cos x}\sim_0\frac{\sqrt{1+x+\frac{x^3}3} - \sqrt{1+x-\frac{x^3}6}}{x+\frac{x^2}2}\sim_0\frac{\frac{1}{2}\left(\frac{x^3}3+\frac{x^3}6\right)}{x}\sim_0\frac14 x^2$$ so the desired limit is $0$.

Edit Without Taylor series the calculus is tedious: let $$f(x)=\sqrt{1+\tan x} - \sqrt{1+\sin x}$$ and $$g(x)=1+x-\cos x$$ then $$\lim_{x\to0}\frac{\sqrt{1+\tan x} - \sqrt{1+\sin x}}{1+x-\cos x}=\lim_{x\to0}\frac{f(x)-f(0)}{x-0}\frac{x-0}{g(x)-g(0)}=\frac{f'(0)}{g'(0)}$$ and with painful calculus we find that $f'(0)=0$ and easily $g'(0)=1$ so we conclude.

$\endgroup$
  • $\begingroup$ You can't use taylor series as OP said. $\endgroup$ – Euler....IS_ALIVE Feb 19 '14 at 6:17
  • $\begingroup$ What I have done in the edit is correct? And I like your second method :) $\endgroup$ – Sawarnik Feb 19 '14 at 6:33
  • $\begingroup$ @Sawarnik Yes correct! $\endgroup$ – user63181 Feb 19 '14 at 6:35
  • $\begingroup$ @SamiBenRomdhane Thanks :) $\endgroup$ – Sawarnik Feb 19 '14 at 6:36
  • $\begingroup$ You're welcome:) @Sawarnik $\endgroup$ – user63181 Feb 19 '14 at 6:37
0
$\begingroup$

$$\lim_{x\to 0}\frac{\sqrt{1+\tan x}-\sqrt{1+\sin x}}{1+x-\cos x}$$ Here the form is $(\frac{0}{0})$, so we can apply L'hospital rule. $$\lim_{x\to 0}\frac{\frac{1}{2\sqrt{1+\tan x}}\sec^{2}x-\frac{1}{2\sqrt{1+\sin x}}\cos x}{1+\sin x}=0.$$

$\endgroup$
  • 1
    $\begingroup$ What about "cannot use LH" part? :) $\endgroup$ – Kaster Feb 19 '14 at 6:26
  • $\begingroup$ Taylor Series and Lhopital's rule can't be used. $\endgroup$ – Euler....IS_ALIVE Feb 19 '14 at 6:28

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.